Fitting Community Based Newborn Care Package into the health systems of Nepal - Pradhan, Y V; Upreti, S R; KC, N P; Thapa, K; Shrestha, P R; Shedain, P R; Dhakwa, J R; Aryal, D R; Aryal, S; Paudel, D C; Paudel, D; Khanal, S; et al. (Journal of Nepal Health Research Council, 2011)
Community-based strategies for delivering effective newborn interventions are an essential step to avert newborn death, in settings where the health facilities are unable to effectively deliver the interventions and reach their population. Effective implementation of community-based interventions as a large scale program and within the existing health system depends on the appropriate design and planning, monitoring and support systems. This article provides an overview of implementation design of Community-Based Newborn Care Package (CB-NCP) program, its setup within the health system, and early results of the implementation from one of the pilot districts. The evaluation of CB-NCP in one of the pilot districts shows significant improvement in antenatal, intrapartum and post natal care. The implementation design of the CB-NCP has six different health system management functions: i) district planning and orientation, ii) training/human resource development, iii) monitoring and evaluation, iv) logistics and supply chain management, v) communication strategy, and vi) pay for performance. The CB-NCP program embraced the existing system of monitoring with some additional components for the pilot phase to test implementation feasibility, and aligns with existing safe motherhood and child health programs. Though CB-NCP interventions are proven independently in different local and global contexts, they are piloted in 10 districts as a â€œpackageâ€ within the national health system settings of Nepal. Keywords: Nepal, community-based newborn care package, health system management, pay-for-performance.